ARTIFICIAL INTELLIGENCE CONTROLLED RELAXATION SYSTEM FOR AUTISTIC CHILDREN – IT TECHNOLOGY THAT ADDRESSES SOCIAL ISSUES - Macerauskas, Eugenijus; Žalys, Vytautas; Lucun, Andzej; Tumasonis, Romanas; Laukhammer, Eivin; Kozič, Antoni (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article presents the development and research of technological tools - a relaxation system for children with autism. The article describes the means and methods of emotional stabilization of children with autism spectrum disorders. The design, operation, and control of the relaxation system controlled by artificial intelligence with image processing and machine learning are described. The relaxation effect on children is carried out with audio-musical signals, by combining them with colored light and mechanical vibration of the back area. The practical research results are described, demonstrating the system's effectiveness for children with autism spectrum disorders. Under normal conditions, if a child takes 3 to 4 hours to calm down, the relaxation system shortens this time to 10 to 15 minutes. Finally, the relaxation system controlled by artificial intelligence-based software, created by scientists from three Lithuanian universities and the students of Vilnius Kolegija, is presented as a technological tool designed to address social issues in society.